Physicochemical properties of premix ice cream from brown rice (Oryza Saliva) and barley (Hardman Vulgare) - Thivashini Kanasan (2022)
A few ingredients are required to produce ice creams such as creamer, sugar, salt, water, flavour, essence, and milk derived from an animal. Barley and brown rice provide the creaminess and categories as wheat, barley, and brown rice used as an alternative milk ingredient to produce healthy and vegan ice cream. Greater content of nutrients such as protein, lipids, minerals, and vitamins were contained in brown rice. Both soluble and insoluble fibre, protein, vitamins B and E, the minerals selenium, magnesium and iron, copper, flavonoids, and anthocyanin are contained in barley. Hence, this study was aimed to produce ice cream from brown rice (Oryza saliva) and barley (Hordeum vulgare L.). This product is majorly developed for the vegan, lactose intolerant, and health-conscious population. Physicochemical properties such as viscosity, pH value, protein, fibre and fat analysis were analyzed using the standard method. Furthermore, the sensory evaluation test determine consumer acceptance toward the brown rice and barley premix ice cream product. Based on the result, the range of the fat content of the brown rice and barley premix ice cream are 33.66 to 34.66 which are lower than the control. As for the protein content, the range of protein content of brown rice and barley ice cream premix are 0.88 to 0.93 which are higher than the control. While, the range of the 2.66 to 4.66 which are also higher than control. The range of the ash content of brown rice and barley premix ice cream are 0.92 to 0.96 which are higher than the control. This indicate that the brown rice and barley premix ice cream contain higher mineral content. According to the moisture content result, the range moisture content is 3,86 to 4.16. The range of the pH are 4.66 to 4.70. The range of the viscosity of the brown rice and barley premix ice cream are 3,14 to 3.44. As for the sensory evaluation brown rice and barley premix ice cream with raspberry flavour was chosen as the best formulation in terms of aroma, colour, taste, texture and overall acceptance. Hopefully, the development of this product can be one of the solutions to the vegan, lactose intolerant, and health-conscious population.